A high strength, wear and corrosion-resistant, antibacterial and biocompatible Nb-5 at.% Ag alloy for dental and orthopedic implants. (30th July 2021) - Wan, Tian; Chu, Kangjie; Fang, Ju; Zhong, Chuanxin; Zhang, Yiwen; Ge, Xiang; Ding, Yonghui; Ren, Fuzeng
Graphical abstract: Highlights: A nanostructured Nb-5 at.% Ag alloy was fabricated by mechanical alloying and spark plasma sintering. Adding 5 at.% Ag significantly enhanced the mechanical properties of Nb, with compressive yield strength of 1486 MPa and fracture strain of 35 %. The higher Ag amount induced the precipitation of larger Ag particles and would reduce friction and wear. The corrosion resistance was significantly improved after adding Ag into the Nb matrix. The obtained Nb-5 at.% Ag alloy shows strong antibacterial activity and good biocompatibility and osteointegration ability. Abstract: Refractory metal niobium (Nb) incorporated with a small amount of silver (Ag), the resulting Nb-Ag two-phase alloys, were fabricated by mechanical alloying and spark plasma sintering. The microstructure, mechanical properties, wear resistance, corrosion behavior, in vitro and in vivo antibacterial properties and biocompatibility of the Nb-Ag alloys were systematically investigated. The results show that the mechanical properties, wear resistance, corrosion resistance and antibacterial ability were significantly enhanced after addition of 5 at.% Ag. The fabricated Nb-5 at.% Ag alloy demonstrates high yield strength of up to ∼ 1486 MPa and fracture strain of ∼ 35 %. The precipitated Ag particles could reduce friction and wear. The enhanced corrosion resistance was attributed to the higher relative density of the sintered alloys and the formation of a stable and dense passive film of niobium and silver oxides. In vitro and in vivo evaluations show that the Nb-5 at.% Ag alloy also has strong antibacterial activity and good biocompatibility and osteointegration ability. These results demonstrate great potential of the nanostructured Nb-Ag alloys for dental and orthopedic implants.